Effect of Nano Fuel Additives on the Characteristics of Diesel Engine Fed with Biodiesel Blended Fuel (Journal of University of Babylon for Engineering Sciences, 2019)
A Numerical analysis for the effect of different Nano particles concentrations on the diesel engine characteristics fired with biodiesel blended fuel is investigated in the work. The simulation software Diesel-rk has been used in this work. The biodiesel under focus is castor methyl ester (CME) which is derived from castor oil via transesterification process. The impact of Nano particles is studied by using three doses of Al2O3 (25, 50, 100 ppm) mixed with B20% CME which is confirmed from previous studies as the best compromise ratio. Generally it's found that with use of Nano particles along with biodiesel fuel, the cylinder pressure, delay period, combustion temperature decreases. Noticeable enhancements in the brake thermal efficiency and fuel consumption have been recorded.  The results reported dramatic reductions in smoke values, NOx emissions as well as Particulate matter (PM), hence this way can fight trade-off relation (PM-NOx). The findings showed, best concentration of Nano particles was 25 ppm as no dramatic effect was observed beyond this dose. The validity of the numerical results is checked out with other experimental results at the same condition of operation.